Awareness of fasciolosis among household dairy farmers in Boyolali, Indonesia - Kurnianto, Heri; Ramanoon, Siti Zubaidah; Aziz, Nor Azlina; Indarjulianto, Soedarmanto; Hayati, Rini Nur (Faculty of Veterinary Medicine, University of Tripoli, 2025)
Background: Fasciolosis is a global parasitic disease that causes enormous economic losses in the ruminant industry by affecting the production of meat and milk. Farmers play an influential role in mitigating the parasite’s lifecycle because cattle are a common host of the parasite. Aim: This study evaluated the awareness and knowledge of dairy farmers in Boyolali regarding fasciolosis. Methods: A cross-sectional survey was conducted in a dairy farming center in Boyolali, Indonesia, among 72 farmers who were recruited conveniently and interviewed using a structured questionnaire. Chi-square test and multivariate logistic regression were used to analyze the association between the independent and dependent variables. The significance level was set at a p-value of <0.05. Results: Forty-eight (66.7%) respondents had ever heard of fasciolosis. The educational level of the respondents was significantly associated with their awareness of fasciolosis (χ2 = 10.06, df = 1, p = 0.002). Farmers with a higher level of education were more likely to be aware of fasciolosis than those with a basic level of education [odds ratio (OR) = 5.80, 95% CI 1.85–18.18]. Nevertheless, 44 (61.1%) farmers were aware of the disease but demonstrated a lack of knowledge. Farmers with basic educational levels (OR = 0.16, 95% CI 0.05–0.52), and herd size less than five (OR = 0.31, 95% CI 0.10–0.95) were more likely to have poor knowledge of fasciolosis. Conclusion: Despite the relatively high level of fasciolosis awareness among dairy farmers, a knowledge gap remains. Periodic extension programs are recommended to improve the knowledge of farmers about fasciolosis and its control and prevention.